Nilai Karakter Nasionalis dan Gotong Royong dalam Novel Guru Aini Karya Andrea Hirata - Lathifah Nurul Hidayah; Nafron Hasjim; Ali Imron Al-Ma’ruf (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This article describes nationalist character value and mutual cooperation character value in the novel “Guru Aini” by Andrea Hirata. The approach of this study is qualitative descriptive. The data in this study are words, phrases, and sentences that contain nationalist character value and mutual cooperation character value in the novel “Guru Aini” by Andrea Hirata. The data source of this study is the novel “Guru Aini” by Andrea Hirata. The data collected in this study used the documentation method, observation, and note-taking technique. The data analysis in this study used the referential equivalent method. This study showed three nationalist character values and five mutual cooperation character values in the novel “Guru Aini” by Andrea Hirata. The three nationalist character values, namely the character of self-sacrifice, the character of excellence and achievement, and the character of discipline. The five mutual cooperation character values were found, namely the character of respect, the character of help, the character of empathy, the character of anti-discrimination, and the character of volunteerism. The dominant character value in the novel is the character of volunteerism.